MOLEonline: a web-based tool for analysing channels, tunnels, and pores (2025 update) - Raček, Tomáš; Vel'ký, Dušan; Bučeková, Gabriela; Schindler, Ondřej; Hutařová Vařeková, Ivana; Špačková, Anna; Bazgier, Václav; Berka, Karel; Svobodová, Radka (Bioinformatics (Oxford, England), 2025)
SUMMARY: MOLEonline is an interactive, web-based tool designed to detect and analyse channels (pores and tunnels) within protein structures. The latest version of MOLEonline addresses the limitations of its predecessor by integrating the Mol* viewer for visualization and offering a streamlined, fully interactive user experience. The new features include colouring tunnels in the 3D viewer based on their physicochemical properties. A 2D representation of the protein structure and calculated tunnels is generated using 2DProts. Users can now store tunnels directly in the mmCIF file format, facilitating sharing via the community-standard FAIR format for structural data. In addition, the ability to store and load computation settings ensures the reproducibility of tunnel computation results. Integration with the ChannelsDB 2.0 database allows users to access precomputed tunnels. AVAILABILITY AND IMPLEMENTATION: The MOLEonline application is freely available at https://moleonline.cz with no login requirement, its source code is stored at GitHub under the MIT licence at https://github.com/sb-ncbr/moleonline-web, and archived at Figshare at https://doi.org/10.6084/m9.figshare.29816174.
Keywords: Software; User-Computer Interface; proteiny; Computational Biology; databáze proteinů; uživatelské rozhraní počítače; internet; výpočetní biologie; Protein Conformation; konformace proteinů; Proteins; Databases, Protein; software; Internet